Pengaruh Kompetensi Supervisor, Variasi Metode Supervisi, Dan Persepsi Supervisor Terhadap Kemampuan Mengajar Guru Bidang Studi Ekonomi SMA Se Kabupaten Katingan - Uliyani; Helmuth Y Bunu; I Ketut Muder (Edunomics Journal, 2020)
This study aims to Analyze the influence of supervisor's competence on teacher's teaching ability in the field of economic studies of katingan districts Analyzing the influence of variation of supervisory methods used by the supervisor to the teaching ability of the teacher of economics studies of katingan district; Analyzing The influence of supervisor 'perceptions of the benefits of supervision on teachers' teaching ability in the field of economic studies as regencies of katingan; And Analyzing Effect of supervisor's competence, variation of supervision method, mutual supervision benefit to teacher's teaching ability in economy study area katingan district. The sample in this research is 40 teachers. This research uses quantitative explanatory approach and data collection by survey method. Data were collected using questionnaires with Likert scale 1-5. The data analysis technique used is multiple linear regression analysis with the help of SPSS program. The results of this study prove that 1) The competence of supervisors have a significant effect on the ability of teaching economics teacher of SMA Se Kabupaten Katingan. The magnitude of influence is 0.235. These results indicate that the higher the supervisor's competence will improve the teaching ability of the teacher. 2) Variations of teaching methods used by supervisors have a significant effect on teachers' teaching ability. The magnitude of influence is 0.159. These results indicate that the more varied teaching methods used by supervisors will improve teachers' teaching ability. 3) The supervisor perception of the benefits of supervision has a significant effect on teachers' teaching ability. The magnitude of influence is 0.159. This result shows that supervision is very useful to improve teachers' teaching ability. 4) The simultaneous test results indicate that the supervisor's competence, the variation of Supervision methods and the benefits of supervision together have a significant effect on teacher's teaching ability with FStatistic> FTable (66.382> 2.866) or significance value (P <0.05).